Scientific Advisor on entrepreneurship - Souleles, Nicos (My University, 2026)
SYNTHESIS Center for Research and Education, Scientific Advisor on entrepreneurship, social innovation and social design. Scientific Advisor for the project ‘Migrant ENPower’.